Three-Year Outcomes of Combined Autotransplantation and Regenerative Endodontic Treatment of an Immature Tooth: A Case Report - İdil Özden; Emrah Canbazoğlu; Hesna Sazak Öveçoğlu (European Annals of Dental Sciences)

(untitled)
Autotransplantation and regenerative endodontic treatment are biologically based dental treatment modalities.Autotransplantation may be a more affordable alternative to implants for patients who experience tooth loss at a young age.Regenerative endodontic treatment is also an alternative to routine endodontic treatment as it can allow the regeneration ofnecrotic or inflamed pulp tissue. The aim of this case is to report a successful 3-year treatment outcome in an immature toothusing a combination of autotransplantation and regenerative endodontic treatment. An 18-year-old female patient withcomplaints of severe pain and mobility at 37. The patient’s medical history revealed no systemic disease. Clinical and radiographicexamination revealed that 37 had undergone root canal treatment 3 years ago. Retreatment of the root canal was initiated, but thesymptoms did not improve despite interm treatment. After surgical consultation, it was decided to extract 37. Forautotransplantation, 38 was extracted atraumatically and autotransplanted into the socket of 37 and splinted for 2 weeks.Regenerative endodontic treatment was planned due to the radiolucency observed in the periapical area of the tooth at the6-month follow-up. Regenerative endodontic treatment was performed on the autotransplanted tooth using platelet-rich fibrinobtained from the patient’s own blood. The tooth remained asymptomatic and functional for 3 years. Root development continuedand periapical healing was complete at 6 months. The tooth showed a positive response to pulp sensitivity tests at the 1-yearfollow-up. The combination of autotransplantation and regenerative endodontic treatment can be considered as a long-termtreatment option for immature teeth.Keywords: Autotransplantation; Regeneration; Revascularisation; PRF; Vital pulp therapy